Pengembangan Sistem Manajemen Bimbingan di Program Studi Teknik Informatika Universitas Pamulang - Suci Fitriyana; Aries Saifudin (Program Studi Teknik Informatika Universitas Pamulang, 2018)
Time becomes the main problem in doing guidance. Because students and lecturers collide with each other in time to conduct guidance, which makes the completion of the student's final assignment delayed. So that it makes it difficult for supervisors and study program officials to see the development of students who do guidance. Application to deal with time clashing with each other in guidance and the difficulty of seeing the development of guidance students. Thus, a guidance management system is created that can reduce the problem. This management system makes it easy for students and lecturers to carry out guidance at any time without having to clash time and come to campus, supervisors and study program officials are easy to see the development of student guidance without having to meet directly.